2018
DOI: 10.1038/s41419-018-1018-7
|View full text |Cite
|
Sign up to set email alerts
|

Proscillaridin A exerts anti-tumor effects through GSK3β activation and alteration of microtubule dynamics in glioblastoma

Abstract: Glioblastoma (GBM) is characterized by highly aggressive growth and invasive behavior. Due to the highly lethal nature of GBM, new therapies are urgently needed and repositioning of existing drugs is a promising approach. We have previously shown the activity of Proscillaridin A (ProA), a cardiac glycoside inhibitor of the Na(+)/K(+) ATPase (NKA) pump, against proliferation and migration of GBM cell lines. ProA inhibited tumor growth in vivo and increased mice survival after orthotopic grafting of GBM cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…Through its C-terminal part, EB1 interacts with numerous partners at growing MT ends to form molecular networks that contribute to the regulation of MT dynamic instability and regulate MT functions [37]. In addition, the amount of EB1 influences the way MT dynamic instability is altered [38] and posttranslational modifications of EB1 also modulate the regulation of MT dynamics, proliferation /migration and subsequent MTA response [23,38,39]. Interestingly, www.oncotarget.com VEGF suppressed MT dynamics in living HUVECs, induced EB1 C-terminal detyrosination and increased EB1 comet length.…”
Section: Discussionmentioning
confidence: 99%
“…Through its C-terminal part, EB1 interacts with numerous partners at growing MT ends to form molecular networks that contribute to the regulation of MT dynamic instability and regulate MT functions [37]. In addition, the amount of EB1 influences the way MT dynamic instability is altered [38] and posttranslational modifications of EB1 also modulate the regulation of MT dynamics, proliferation /migration and subsequent MTA response [23,38,39]. Interestingly, www.oncotarget.com VEGF suppressed MT dynamics in living HUVECs, induced EB1 C-terminal detyrosination and increased EB1 comet length.…”
Section: Discussionmentioning
confidence: 99%
“…They mirror a realistic in vitro scenario of tumor growth and invasion [50]. Furthermore, they are widely adopted for high-throughput drug screening since they are easy to handle and engineer [50][51][52]. Spheroids are usually derived from GB cell lines growing as spheres in a 3D matrix or in suspension.…”
Section: Spheroidsmentioning
confidence: 99%
“…In particular, increased MMP levels and tumor invasiveness in human GBs show a strong correlation (12,30,31). Several studies reported their localization in TM membrane (32,33), especially for MMP-2 and MT1-MMP.Our interest arises from the analysis of the role of TMs in tumor progression and of the effect of different drugs on their structures and dynamics (34,35). The inhibition of TMs leads to a decrease in cell migration and proliferation, with obvious consequences on GB treatment (34)(35)(36).…”
mentioning
confidence: 99%
“…Several studies reported their localization in TM membrane (32,33), especially for MMP-2 and MT1-MMP.Our interest arises from the analysis of the role of TMs in tumor progression and of the effect of different drugs on their structures and dynamics (34,35). The inhibition of TMs leads to a decrease in cell migration and proliferation, with obvious consequences on GB treatment (34)(35)(36). The process of growth and retraction of TMs plays a fundamental role for cell-to-cell communication routing (17,18,(20)(21)(22)(23), as well as a transient binding platform for essential proteins that regulate tumor dynamics (37).…”
mentioning
confidence: 99%
See 1 more Smart Citation